Role of Strategic Marketing on Competitive Advantage for E-Commerce Business in India: An Empirical Study - Dr. Kamlesh Babu Gautam , Dr. Krishna Kumar Verma, Dr. Jyoti Kumari Mishra; Kumar, Dr. Manish (Journal of Informatics Education and Research, 2024)
Strategic competitive strategy equips executives with practical knowledge, new skills, and tools to translate strategic ideas into actionable plans. Within strategic research, competitive research focuses on gathering information about rival firms, a crucial approach to assess their activities and potential threats to financial strength. Despite the rapid development of electronic commerce, many e-commerce businesses are still in the investment and brand-building phase, struggling to show a profit. Strategic marketing plays a pivotal role in attaining organizational goals and objectives, aiding in the identification and implementation of new opportunities. The decisions made by management can make significant effect on the performance of e-commerce businesses in India. Strategic marketing management is a defined as a process that involves identifying company goals, creating effective strategies, and implementing them to achieve those goals. A sample of 233 respondents was collected from people working in e-commerce businesses in India. The variables that identify the role of Strategic Marketing on Competitive Advantage for E-Commerce Business in India are Innovation and Adaptability, Brand and Market Positioning, Customer Segmentation, and Competitive Pricing and Promotions.